Pay enough, don't pay too much or don't pay at all? The impact of bonus intensity on job satisfaction - Konstantinos Pouliakas (Institute for the Study of Labor (IZA), 2010)
Using ten waves (1998-2007) of the British Household Panel Survey (BHPS), this paper investigates the ceteris paribus association between the intensity of incentive pay, the dynamic change in bonus status and the utility derived from work. After controlling for individual heterogeneity biases, it is shown that job utility rises only in response to 'generous' bonus payments, primarily in skilled, non-unionized, private sector jobs. Revoking a bonus from one year to the next is found to have a detrimental impact on employee utility, while job satisfaction tends to diminish over time as employees potentially adapt to bonuses. The findings are therefore consistent with previous experimental evidence, suggesting that employers wishing to motivate their staff should indeed pay enough or don't pay at all.
Keywords: C23; J28; J33; M52; M54; 330; Incentives; intensity; bonus; performance pay; job satisfaction; Leistungsorientierte Vergütung; Erfolgsbeteiligung; Arbeitszufriedenheit; Großbritannien